Cyclic fatigue resistance of three reciprocating nickel-titanium instruments with heat treatment at intrachannel temperature - Portillo-Martínez, Maria Alejandra; Horta-Dos Santos, Luiz Meton; Rangel-Do Couto, Viviane; Frozoni, Marcos; Mendez, Julieta (Revista Facultad de Odontología Universidad de Antioquia, 2023)
Introduction: the in vitro study compared the dynamic cyclic fatigue resistance of 3 reciprocating NiTi files with heat treatment. Methods: we distributed 30 new endodontic files in three groups. The endodontic files selected for this experiment were: AF Blue R3 25/06 (AFB) (Fanta Dental, Shanghai, China), X1 Blue File 25/06 (X1B) (MK Life, Porto Alegre, RS, Brazil), and Reciproc Blue 08/25 (RB) (VDW, Munich, Germany. We measured the time to file fractureand the length of the fractured fragment. ANOVA analysis was used, followed by the Tukey test for multiple comparisons, with a significance level of 5% (P < 0.05). Results: the mean time in seconds until the file fractured was 170.7 ±15.1 for AFB files, 110.4 ±26.8 for X1B, and 163.3 ±22.9 for RB files. This difference was statistically significant when comparing X1B to AFB (p: 0.000) and X1B to RB (p: 0.000). However, there are no statistically significant differences between RB and AFB (p:0.739). Conclussions: this study found that RB and AFB files exhibit similar resistance to cyclic fatigue.